Exploring intelligent hospital management mode based on artificial intelligence - Dezhi Mi; Yong Li; Kangying Zhang; Chaoni Huang; Wenjia Shan; Jiangbo Zhang (Frontiers Media S.A., 2023)
ObjectiveTo address the challenges posed by the COVID-19 pandemic, our hospital developed an intelligent hospital management mode specifically tailored to COVID-19 patients.MethodsThis study included patients with confirmed diagnosis of COVID-19 admitted to our hospital between January 2020 to December 2022. We sought to explore intelligent hospital management mode based on artificial intelligence (AI) and new technologies such as 5G, Internet of Things (IoT), wearable devices, robots, and small programs.ResultsIntelligent hospital management mode can help improve the quality of life of patients, while also improving the management ability of the hospital, as it can automatically deliver timely patient reminders, maintain environmental cleanliness, and help in the transportation of medical equipment without any manual labor. This can help in conserving time and reducing the workload of medical staff. Moreover, itcan help intellectualize patient admission, patient discharge, and hospital management, thereby helping in providing efficient medical and patient humanistic care.ConclusionsThe development of intelligent management mode can reduce the burden of medical personnel and the probability of developing infection and bring about timely and better patient care. Intelligent management can play a pivotal role in control of the epidemic, treating patients, allocation of resources, tracing the root cause of the virus, and monitoring.